The nature of normativity - Wedgwood, Ralph (Oxford : Clarendon, 2007)
Presenting a complete theory about the nature of normative thought - that is, the sort of thought that is concerned with what ought to be the case, or what to do or think, Ralph Wedgwood defends a kind of realism about the normative according to which normative truths or facts are genuinely part of reality.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Normativity (Ethics)